International experiences in developing environmental performance index and possible application in Vietnam - Lam, Nguyen Tung (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Environmental sustainability has been identified as important content and orientation in socio-economic and environmental development policies in our country. Reviewing the implementation of sustainable development goals of these policies, as well as environmental policies will provide the basis for process of planning, revision and monitoring of the progress of implementation of policies by central, local agencies concerned. In the world, the method of assessment of environmental performance based on reliable collected data has been developed and tested at national level, the approach of this may be used to elaborate a method of evaluation at local level. This paper introduced international experiences in developing global Environmental Performance Indicators and the possibility of develop them in the context of Vietnam. Code: 15052102